Roles of lipocalin 2 and adiponectin in iron overload cardiomyopathy - Natthaphat Siri-Angkul (2018)
© 2017 Wiley Periodicals, Inc. Thalassemia is among the most common genetic diseases worldwide. Ineffective erythropoiesis, chronic hemolysis, and regular blood transfusion in thalassemia patients lead to increased iron burden. Iron overload cardiomyopathy is the most severe co-morbidity and most common cause of mortality in thalassemia patients. Although its associated mechanisms are still not completely understood, cellular iron mishandling, chronic inflammation, and oxidative stress appear to be the key processes involved. In order to acquire a more comprehensive insight of the impact of cardiac iron overload, these alterations need to be intensively investigated. This comprehensive mini-review focuses on two emergent molecules which have been shown to potentially play significant roles in iron overload cardiomyopathy. These two molecules are an iron-transporting protein, lipocalin 2, and an anti-inflammatory adipokine, adiponectin. Reports from in vitro and in vivo studies are comprehensively summarized. Clinical studies examining the roles of these molecules in thalassemia patients are also presented and discussed.